The Imbalance in Serum Concentration of Th-1- and Th-2-Derived Chemokines as One of the Factors Involved in Pathogenesis of Atopic Dermatitis - Joanna Narbutt; Aleksandra Lesiak; Anna Sysa-Jedrzeiowska; Marcin Zakrzewski; Jarosław Bogaczewicz; Iwona Stelmach; Piotr Kuna (Hindawi Limited, 2009)
Atopic dermatitis (AD) is an inflammatory skin disease in which pathogenesis chemokines are partially involved. The aim of the paper was to assess the serum level of CXCL-9, CXCL-10, CXCL-11, CXCL-12, CCL-17, CCL-20, CCL-21, CCL-22, CCL-27, and IL-18 chosen in AD patients by ELISA assay. Forty patients (mean age 11.4 years old) with AD and 50 healthy controls were enrolled into the study. The patients and controls were divided into two age categories: under 10 years old (Group 1 and Control 1) and over 10 years old (Group 2 and Control 2). Significantly lower serum concentration of CXCL-9, CXCL-10, CCL-17, and IL-18 and higher concentration of CXCL-12 and CCL-27 were found in Group 1 when compared to Control 1. In Group 2 serum concentration of CXCL-12, CCL-17, CCL-22 was higher than in Control 2. The obtained results indicate the imbalance in chemokine serum levels in AD what suggests their role in the disease pathogenesis.